Patients Satisfaction regarding Quality of Nursing Care in the National Center for Diabetes, Endocrinology and Genetics in Amman, 2013 (Journal of Basic and Applied Research in Biomedicine, 2022)
It is important for any health system to provide high quality health Nursing services and respond to the needs of service users. The aims of this study is to study patients' satisfaction regarding the quality of nursing care of the center, to identify the main dimensions of patients' satisfaction regarding quality of nursing care. And determine the association between sociodemographic variables and patients' satisfaction regarding quality of the nursing care. This study was conducted during the period from1st December 2013 to 1st may 2014. The design of this study is Descriptive cross-sectional facility based study. The study sample 305 patients, who were selected randomly, all of them actually participated in the study and completed face to face interviewed questionnaire prepared according to Likert scale and data was analyzed by SPSS. Participants were moderately satisfied with the quality of nursing care in the National Center for Diabetes Endocrinology and Genetics. The total mean was (3.09), with higher satisfaction levels in the General impressions (M = 3.83) than in Communication, interaction and reaction (M = 2.57). Patients from both settings were less satisfied with the Accessibility of services (M = 2.89). Age, sex, marital status, level of education, income, and the diagnosis show statistically significant effects on patients' level of satisfaction. On the other hand duration of diabetes, and current occupation did not show statistically significant effects on patients' level of satisfaction. The present study concluded that reforming community health nursing care policies to place more attention on increasing the level of communication and the interpersonal aspects of the provided care could probably increase their satisfaction. And the geographical redistribution of community diabetes health center to enable the patient's easy access to nursing services in all Jordan regions, increase number of home visits, for the patients' nursing team need to improve communication, interaction skills of nursing care staff and in formats. Nursing team needed training for nurses on communication skills and interaction with patients and their families.